A young female with hypocomplementemic urticarial vasculitis associated with a rare CNS manifestation. Issue 2 (April 2023) - , Safi Alqatari, Manal Hasan, Raed Bukhari Fatimah Alabdrabalnabi; Hadhiah, Kawther, Fatimah Al Ohaid, Abrar Alwaheed; Aldarwish, Abdullah W
No abstract available